ASSESSMENT OF HEAVY METAL CONTAMINATION IN SOIL SAMPLE NEAR INDUSTRIAL AREA OF MORBI, GUJARAT (International Association of Biologicals and Computational Digest, 2022)
The quantities of toxic trace metals in soil have a significant impact on soil quality and its usage in food production, particularly in an industrial Area. Toxic elements such as copper, zinc, and iron, as well as Manganese, are investigated in representative soil samples from Morbi, Gujarat's industrial sector. Sample were taken from five different location near industrial area it were compared to the Gujarat government's test range, most of the industrial region is significantly contaminated bycopper, and zinc, with partial contamination by manganese and iron.
Keywords: Soil, Heavy metal, Contamination, Industry, Morbi